The diffusion of minimum tillage in agricultural China : a study of the factors influencing the farmers’ choice of tillage system - Andersson, Jenny; Halvarsson, Marcus (SLU/Dept. of Economics, 2013)
The Chinese government´s aim to be self-sufficient in food production in combination with the increased food consumption in China has put high pressure on the productivity within the Chinese agricultural sector (He j et al, 2010). In order to increase the productivity, modernization and adoption of new farming techniques are essential. The opportunity to adopt and import foreign technology has lately been possible in China, as more authority and decision rights have been given to the individual farmers and the country has opened up for foreign trade (Zheng, 2012 & Fan, 1991). A more open Chinese market enables new opportunities for foreign agricultural companies to expand their businesses by introducing their products to Chinese farmers. But to succeed with this strategy the Chinese farmers must be willing to adopt these, for them new innovations. Minimum tillage is a tillage practice used worldwide that is suitable in northern China where drought and erosion are the main problems in the crop production (pers.com., Arvidsson, 2012).